Quality of Educational Facilities and Graduate Employability Competences in Lagos State Nigeria - Esther Oshionebo; Olawale Owolabi (Universitas Ahmad Dahlan, 2022)
This research work examined the relationship between quality of educational facilities and graduate employability competence in Lagos state. The study was carried out in different NYSC zones using 256 NYSC members which are selected through the simple random sampling techniques from the different NYSC zones in Lagos State. In order to achieve the aim of this study, 3 research questions and 2 hypotheses were formulated. A questionnaire titled quality of educational facilities and graduate employability competences (QEFGEC) was developed by the researchers. The research instrument was administered through google form, the questionnaire was designed online and responses were gathered online. Before the instrument was administered, it was subjected to face and content validity by 2 professionals in the field of Educational Management and Measurements and Evaluation in University of Lagos and Ekiti State University. Also, in ensuring the reliability of the used instrument, a pilot test was carried out using 20 NYSC members in Lagos. Using the Cronbach’s alpha reliability method, the instrument had a reliability coefficient of 0.74. The instrument was self-administered to the respondents and responses were gathered within few days due to the aid of ICT. The data gathered on the research questions from the field was analyzed using a simple percentage, means, standard deviation while the research hypothesis was tested using inferential statistics. It was discovered that there is a significant relationship between availability, utilization of educational facilities and graduate employability competences. It was therefore recommended that Tertiary institution head must ensure that all needed facilities are provided for effective utilization by the teachers and students, also Government and all education stakeholders should provide adequate funding for the tertiary institution because without quality output, the objective of education in national development will not be achieve and lastly Student and lecturers should be encouraged to use, manage and maintain the limited educational facilities provided adequately